7x-5=5x+23
7x-5x=23+5
2x=28
x=28/2
x=14
-1 = (x-1)/3
(multiply both sides by 3)
-3 = x-1
(add 1 on both sides)
x=-2
The <span>expression that represents n plus 7 multiplied by 3 is
(n + 7)(3)
The entire expression, (n + 7) is multiplied by 3 since it would be inconvenient to state the expression as given above if what is meant was
(n + 7x3). It would have simply been n plus 21.</span>
Answer:
D
Step-by-step explanation:
BecASUE D IS THE NEXT IN THE PATTERN.
Answer:
t = pn
Step-by-step explanation:
We are to find the relationship between total cost and the number of items.
First we would represent the relationship between total cost and number of items with variables
Let the total cost = t
and the number of items = n
Total cost t is proportional to the number n of items:
t ∝ n
t = kn
where k is constant
Since it is purchased at a constant price p, the constant of proportionality would be p. the k would be replaced with p
t = pn